2018
DOI: 10.3390/polym10060564
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Pad-Steam Dyeing of Cotton Fabric Modified with Cationic P(St-BA-VBT) Nanospheres

Abstract: The Poly[Styrene-Butyl acrylate-(P-vinylbenzyl trimethyl ammonium chloride)] P(St-BA-VBT) nanospheres with N + (CH 3 ) 3 functional groups were successfully prepared and applied to modify cotton fabrics using a pad-dry process. The obtained cationic cotton fabrics were dyed with pad-steam dyeing with reactive dye. The results show that the appropriate concentration of nanospheres was 4 g/L. The sodium carbonate of 25 g/L and steaming time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…The treated cotton fabrics showed that a large number of nanospheres were deposited on the surface of the fiber, and the nanospheres on the fiber surfaces did not form a continuous film and were randomly distributed, similar to the previous study [27,37]. Besides, the size of the nanospheres was significantly smaller than the diameter of the cotton fibers, indicating that the cationization of cotton fabrics had little effects on the spread and diffusion of reactive dye ink droplets on the surfaces of fabrics or fibers [15]. Compared to the previously study [18], the cationization of cotton fabrics modified with nanospheres is an effective method for improving the color performance of reactive dyes ink-jet printing.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The treated cotton fabrics showed that a large number of nanospheres were deposited on the surface of the fiber, and the nanospheres on the fiber surfaces did not form a continuous film and were randomly distributed, similar to the previous study [27,37]. Besides, the size of the nanospheres was significantly smaller than the diameter of the cotton fibers, indicating that the cationization of cotton fabrics had little effects on the spread and diffusion of reactive dye ink droplets on the surfaces of fabrics or fibers [15]. Compared to the previously study [18], the cationization of cotton fabrics modified with nanospheres is an effective method for improving the color performance of reactive dyes ink-jet printing.…”
Section: Resultssupporting
confidence: 79%
“…As shown in Figure 6, it can be seen that the K / S values of ink-jet printed cotton fabrics gradually increase as the amounts of NaHCO 3 increase from 1 g/L to 10 g/L, and the maximum K / S value can be achieved when NaHCO 3 amounts achieve 10 g/L. It can be explained that the surface of fabrics become more alkaline with the amounts of NaHCO 3 increases, which can quickly dissociate more hydroxyl groups on the fibers and enhance the degree of reaction with the reactive dyes [15,16], resulting in most of reactive dyes fixing on the fibers. For the cotton fabrics, when the amounts of NaHCO 3 exceed 10 g/L, the K / S values displayed a downward trend, because the excess alkali increased the degree of hydrolysis of the reactive dye.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations